2018
DOI: 10.3389/fendo.2018.00006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Type 2 Diabetes on Bone Fracture Healing

Abstract: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease known by the presence of elevated blood glucose levels. Nowadays, it is perceived as a worldwide epidemic, with a very high socioeconomic impact on public health. Many are the complications caused by this chronic disorder, including a negative impact on the cardiovascular system, kidneys, eyes, muscle, blood vessels, and nervous system. Recently, there has been increasing evidence suggesting that T2DM also adversely affects the skeletal system, cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 131 publications
1
76
1
6
Order By: Relevance
“…Moreover increase Pro-inflammatory mediators including TNF-α, decrease the healing process in diabetes mellitus Jiao H (2011) (21). This was proved by Marin C (2018) (25) who studies the impact of type 2 diabetes on bone fracture healing, he revealed in his study that TNF-α triggers the expression and activity of proapoptotic factors Furthermore, TNF-α contributes to the endothelial cell proliferation impairment, reduced tube formation, and suppressed VEGF expression in fractured tibiae and femora of mice, compromising the angiogenesis of the healing process.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover increase Pro-inflammatory mediators including TNF-α, decrease the healing process in diabetes mellitus Jiao H (2011) (21). This was proved by Marin C (2018) (25) who studies the impact of type 2 diabetes on bone fracture healing, he revealed in his study that TNF-α triggers the expression and activity of proapoptotic factors Furthermore, TNF-α contributes to the endothelial cell proliferation impairment, reduced tube formation, and suppressed VEGF expression in fractured tibiae and femora of mice, compromising the angiogenesis of the healing process.…”
Section: Discussionmentioning
confidence: 90%
“…Although the underlying mechanisms contributing to the decrease in bone strength and bone quality in patients with T2DM are not fully understood, it is known that chronic hyperglycemia led to accumulation of advanced glycation end products that downregulated osteocalcin gene expression and inhibited calcium uptake, which are considered to be involved in the pathogenesis of bone fracture . Moreover, T2DM also has a detrimental effect on bone fracture healing, as it causes delayed healing, non‐union, and postoperative clinical complications such as risk of infection, amputation, or even increased mortality . Many different classes of anti‐diabetic drugs are currently available for the treatment of T2DM, and some of these drugs influence bone metabolism directly and indirectly; therefore, it is critical that anti‐diabetic drugs do not increase the risk of bone fracture …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Moreover, T2DM also has a detrimental effect on bone fracture healing, as it causes delayed healing, nonunion, and postoperative clinical complications such as risk of infection, amputation, or even increased mortality. 8,9 Many different classes of anti-diabetic drugs are currently available for the treatment of T2DM, and some of these drugs influence bone metabolism directly and indirectly; therefore, it is critical that anti-diabetic drugs do not increase the risk of bone fracture. 10 Glucagon-like peptide 1 (GLP-1) is a 30-amino acid peptide hormone secreted from L cells of the gastrointestinal mucosa, which acts as a key determinant of blood glucose homeostasis owing to its capabilities to slow gastric emptying, enhance pancreatic insulin secretion, and suppress pancreatic glucagon secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Обговорення отриманих результатів. На думку Carlos Marin та співавторів, при хронічній гіперглікемії організму порушується узгоджена дія сигнальних молекул та регуляторів транскрипції репаративного остеогенезу, що призводить до зниження функціонування остеобластів, збільшення кількості жирової тканини в складі регенерату та істотного гальмування процесу консолідації переломів [8]. Під час аналізу ранніх стадій процесу остеорепарації ми виявили затримання ліквідації першої фази запалення у тварин із хронічною гіперглікемією організму, як наслідок, на 7-му добу більша частина ділянки дефекту залишалася заповненою некротичним кістковим детритом, фібрином, нейтрофільними гранулоцитами та жировою тканиною.…”
unclassified
“…На фоні хронічної гіперглікемії організму порушуються нео-та ангіогенез, посилюються механізми запалення, що перешкоджають правильному розподілу остеогенних клітин, кисню та поживних речовин у зоні регенерації. Спостерігається порушення катаболізму тканинних структур та проліферації клітинних елементів, які диференціюються в бік адипогенної лінії, збільшуючи вміст жирової тканини в мозолі перелому, а це призводить до процесів гальмування консолідації відламків кісток [8,9].…”
unclassified